2019
DOI: 10.1002/cam4.2736
|View full text |Cite
|
Sign up to set email alerts
|

Desmoplastic melanoma: The role of pure and mixed subtype in sentinel lymph node biopsy and survival

Abstract: Background Desmoplastic melanoma (DM) is an uncommon type of melanoma. Two histological subtypes of DM can be distinguished: pure and mixed (PDM and MDM). We hypothesized that discrimination between these subtypes is associated with sentinel lymph node biopsy (SLNB) status and survival. Methods Clinicopathological data from PALGA, the Dutch Pathology Register were retrieved from patients diagnosed with DM in The Netherlands between 2000 and 2014. Clinical and pathological variables were extracted from patholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Mixed DM is associated with positive SLNB status and a higher frequency of regional metastasis. 22,23 Treatment modalities and the recommendations on the use of SLNB have changed over recent years. The National Comprehensive Cancer Network Cutaneous Melanoma Guidelines currently suggests that clinicians may consider forgoing SLNB in patients with confirmed pure DM because of the controversy of its benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Mixed DM is associated with positive SLNB status and a higher frequency of regional metastasis. 22,23 Treatment modalities and the recommendations on the use of SLNB have changed over recent years. The National Comprehensive Cancer Network Cutaneous Melanoma Guidelines currently suggests that clinicians may consider forgoing SLNB in patients with confirmed pure DM because of the controversy of its benefit.…”
Section: Discussionmentioning
confidence: 99%
“…The distinction between PDM and MDM is also controversial. More studies have found a significantly higher likelihood of nodal metastases in MDM than PDM, 21–24 whereas others have found no difference between their incidence of nodal disease 25 . Consequently and understandably, this has led to diverging opinions with regard to the necessity of sentinel lymph node biopsies for patients with MDM and PDM.…”
Section: Discussionmentioning
confidence: 99%
“…The largest of the 3 additional studies included 239 patients and is limited by the study design using only pathology text files to determine subtype. 5 The study methods further state, "If there was no mention of mixed features, it was assumed there was a pure histologic subtype." 5 Also, 2 studies included in both systematic reviews defined pDM as 80% to 90% desmoplasia, which differs from the widely accepted $90% desmoplasia defined by Busam and colleagues 1,15 Two case series of 58 and 33 patients have recently been published showing no difference in SLNB positivity between pDM and mDM.…”
Section: Discussionmentioning
confidence: 99%
“…4 Because of its subtle clinical presentation, DM can be mistaken for benign neoplasms, including dermatofibroma, scar, or nevus. 5 Diagnosis requires a high index of suspicion followed by appropriate biopsy.…”
mentioning
confidence: 99%
See 1 more Smart Citation